Bone Marrow Stroma Damage Induced by Chemotherapy for Acute Lymphoblastic Leukemia in Children - Corazza, Francis; Hermans, Christophe; Ferster, Alina; Fondu, Pierre; Demulder, Anne; Sariban, Eric (Pediatric research, 2004)
Several studies have suggested a role of bone marrow stroma injury in long-term chemotherapy-induced hematopoietic failure. To evaluate whether bone marrow microenvironment is altered by chemotherapy for acute lymphoblastic leukemia (ALL) and to determine its contribution to postchemotherapy anemia, we investigated the ability of stroma from children receiving maintenance chemotherapy for ALL to support hematopoiesis. Long-term bone marrow cultures (LTBMC) were established with bone marrow cells either from ALL children under therapy (n = 24) or from control subjects (n = 19). Nonadherent cells and colony forming units-granulocytic monocytic (CFU-GM) output in LTBMC did not differ between patients and controls. In contrast, burst forming unit-erythroid (BFU-E) numbers were lower in patient LTBMC (p = 0.013). Co-cultures of normal CD34+ cells and preformed patient or control stromas showed significantly reduced hematopoietic supportive capabilities of patient stromas: both CFU-GM and BFU-E were reduced (p = 0.002 and 0.046, respectively). In addition, supernatants (SN) of patients' LTBMC inhibited normal BFU-E growth compared with SN of normal LTBMC. Transforming growth factor (TGF)-beta1 levels were increased in patient cultures (p = 0.0039) and inversely correlated with BFU-E produced in LTBMC (r = -0.36, p = 0.04). Neutralization of TGF-beta1 significantly increased the BFU-E output of patient LTBMC (p = 0.0078). In contrast, macrophage inflammatory peptide (MIP)-1alpha levels were lower in SN of patients compared with controls (p = 0.015). Thus, chemotherapy for ALL induces functional deregulation within bone marrow stromal cells with an increase in the growth-inhibiting factor TGF-beta1, together with a decrease in MIP-1alpha, which might contribute to hematopoietic toxicity.